Trastornos de escritura y su incidencia en el proceso enseñanza – aprendizaje de los estudiantes del primer año de educación diversificada del colegio técnico agropecuario “José Rodríguez lavandera”, del cantón Quevedo, provincia de los ríos. - Alcívar Vélez, Olga María (2015)
This degree work is to analyze the problem of writing disorders and their impact on the teaching - learning of freshmen Diversified Education Education Unit "Jose Rodriguez Labandera, Quevedo Canton, writing requires Motor interaction mechanisms of visual-spatial integration and kinesthetic control as well as the symbolic foundation of the system of language, moreover, to be writing a not so widely practiced skills such as speech, this research puts much emphasis on the topic for children to develop good writing because it is not only necessary in schools but also in the activities of daily life of each person, to obtain data on this issue a survey was conducted in the institution students which they expressed us their reality and why their poor writing, these data once were analyzed the findings and recommendations were taken, one of which was to propose workshops for teachers and parents on the new teaching-learning with this encourage infants to correct his dysgraphia and get a better academic performance.